Synergistic effects of Pr6O11 and Co3O4 on electrical and microstructure features of ZnO-BaTiO3 varistor ceramics - Shaifudin, Muhamad Syaizwadi; Mohd Ghazali, Mohd Sabri; Wan Mohamad Kamaruzzaman, Wan Mohamad Ikhmal; Wan Abdullah, Wan Rafizah; Kassim, Syara; Ismail, Nur Quratul Aini; Sa’at, Nor Kamilah; Mohd Zaid, Mohd Hafiz; Mohd Fekeri, Maria Fazira; Matori, Khamirul Amin (MDPI AG, 2021)
This paper investigated the effects of Pr6O11 and Co3O4 on the electrical properties of ZnO-BaTiO3 varistor ceramics. The Pr6O11 doping has a notable influence on the characteristics of the nonlinear coefficient, varistor voltage, and leakage current where the values varied from 2.29 to 2.69, 12.36 to 68.36 V/mm and 599.33 to 548.16 µA/cm2, respectively. The nonlinear varistor coefficient of 5.50 to 7.15 and the varistor voltage of 7.38 to 8.10 V/mm was also influenced by the use of Co3O4 as a dopant. When the amount of Co3O4 was above 0.5 wt.%, the leakage current increased from 202.41 to 302.71 μA/cm2. The varistor ceramics with 1.5 wt.% Pr6O11 shows good nonlinear electrical performance at higher breakdown voltage and reduced the leakage current of the ceramic materials. Besides, the varistor sample that was doped with 0.5 wt.% Co3O4 was able to enhance the nonlinear electrical properties at low breakdown voltage with a smaller value of leakage current.